Developing a structural analysis framework utilizing BIM for large scale urban seismic response estimation - Fader, Aileen Rachelle F.
This study focused on developing a Building Information Modeling (BIM)-enhanced assisted framework for large-scale, seismic analysis of structures. The aim of this study was to utilize BIM as input to large scale urban earthquake analysis. Through BIM, information on the three-dimensional geometry, local structural member dimensions and properties, construction information (date of construction, structural code used, etc.) will be available as inputs to structural analysis codes that will compute the response of each building. Thus, in the analysis we inherently account for the vulnerability of the structures in the target area. In this framework, BIM models were used to create structural models for use in static and dynamic analysis. By automating the extraction of data from BIM and utilizing codes for high-performance computing, the seismic response of multiple structures within an area can then be simulated. As an application of this methodology, a typical BIM model corresponding to mid-height and low-height concrete (C1-M & C1-L) buildings was used for simulating the seismic response of similar buildings within an area for a given scenario earthquake.